Primary school teachers’ perceptions of integrating Islamic education into science education - Alharbi , Abdulaziz (Journal of Education and e-Learning Research, 2025)
This mixed-methods study investigates how Saudi primary school teachers view the integration of Islamic values within science curricula in alignment with Vision 2030. Quantitative data were collected from 352 teachers using a structured survey and were complemented by ten in-depth interviews conducted in Al-Madinah Al-Munawwarah. We examined two dimensions: teachers’ conceptual understanding of integration and the importance they assign to embedding Islamic ethics in science, and tested for differences by gender, teaching experience, and academic specialization. Inferential analyses showed no statistically significant demographic differences in conceptual understanding. By contrast, female teachers and those with more years of experience rated the importance of curricular integration significantly higher. Interview narratives illuminated these patterns, describing integration as a means to connect scientific inquiry with students’ moral development and cultural identity, deepening engagement and meaning. These findings point to practical priorities: targeted professional development that models integrative pedagogy; collaborative curriculum work between Islamic studies and science teachers; and supportive policy frameworks that institutionalize ethical reflection alongside scientific competencies. Future research should track cohorts over time and evaluate specific integrative interventions to determine their sustained effects on students’ learning and character development. Overall, the study contributes context-specific evidence from Saudi schools and refines theory on religion–science integration.